2009
DOI: 10.1007/s11270-009-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive Method of Frog (Rana esculenta L.) Skeleton Elemental Analysis Used During Environmental Assessment

Abstract: Amphibians, particularly frogs, are increasingly used as bioindicators of contaminant accumulation in pollution studies. Their use for field scientific purposes is limited because most frog species are endangered and protected in most countries; killing of specimens are not allowed. The aim of our study was to work out and assess a method by which the elemental contents of frog bones could be estimated effectively based on the toe bones. For this purpose, Rana esculenta L. individuals were collected from an ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Among vertebrates, fish, frogs and toads are excellent indicators of heavy metal pollution [8][9][10][11]. Fish, as indicator organisms, are well suited for the monitoring of polluted aquatic ecosystems, since they are able to accumulate all the harmful substances from water and sediment as well as from the food chain [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among vertebrates, fish, frogs and toads are excellent indicators of heavy metal pollution [8][9][10][11]. Fish, as indicator organisms, are well suited for the monitoring of polluted aquatic ecosystems, since they are able to accumulate all the harmful substances from water and sediment as well as from the food chain [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They have reported concentrations of the metals in the order: Fe>Cu and approximately Zn>Mn>Cd. Simon et al (2010) analyzed the trace element concentrations (P, Ca, Mn, S, Na, Mg, Ba and Zn) in R. esculenta bones and on phalanges. Tao et al (2012) found that Zn and Cu are the most likely to be accumulated in all aquatic organisms of different tropic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this kind of survey is not as frequent as research on tadpoles or laboratory research. Considering that over 30 % of amphibian species are threatened with extinction, the attention of researchers is being directed toward non-invasive methods (Simon et al 2009, 2012; Orton et al 2014). The road mortality of vertebrates offers great opportunities for obtaining material for further research (D’Amico et al 2015; Santos et al 2015), including studies on bioindication (Simon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The road mortality of vertebrates offers great opportunities for obtaining material for further research (D’Amico et al 2015; Santos et al 2015), including studies on bioindication (Simon et al 2012). For instance, road-killed toads were used in research on heavy metals absorbed by bone tissues (Simon et al 2009, 2012). …”
Section: Introductionmentioning
confidence: 99%